Changes in expression of sensory organ-specific microRNAs in rat dorsal root ganglia in association with mechanical hypersensitivity induced by spinal nerve ligation - Aldrich, Benjamin T. (2009)
Chronic neuropathic pain caused by peripheral nerve injury is associated with global changes in gene expression in damaged neurons. To understand the molecular mechanisms underlying neuropathic pain, it is essential to elucidate how nerve injury alters gene expression and how the change contributes to the development and maintenance of chronic pain. MicroRNAs are non-protein-coding RNA molecules that regulate gene expression in a wide variety of biological processes mainly at the level of translation. This study investigated the possible involvement of microRNAs in gene regulation relevant to neuropathic pain. The analyses focused on a sensory organ-specific cluster of microRNAs that includes miR-96, -182, and -183. RT-PCR analyses confirmed that these microRNAs were highly enriched in the dorsal root ganglion (DRG) of adult rats. Using the L5 spinal nerve ligation (SNL) model of chronic neuropathic pain, we observed a significant reduction in expression of these microRNAs in injured DRG neurons compared to controls. In situ hybridization and immunohistochemical analyses revealed that these microRNAs are expressed in both myelinated (N52 positive) and unmyelinated (IB4 positive) primary afferent neurons. They also revealed that the intracellular distributions of the microRNAs in DRG neurons were dramatically altered in animals with mechanical hypersensitivity. Whereas microRNAs were uniformly distributed within the DRG soma of non-allodynic animals, they were preferentially localized to the periphery of neurons in allodynic animals. The redistribution of microRNAs was associated with changes in the distribution of the stress granule protein TIA-1. These data demonstrate that SNL induces changes in expression levels and patterns of miR-96, -182, and -183, implying their possible contribution to chronic neuropathic pain through translational regulation of pain-relevant genes. Moreover, stress granules were suggested to be assembled and associated with microRNAs after SNL, which may play a role in modification of microRNA-mediated gene regulation in DRG neurons.